Board of Commissioner and Corporate Social Responsibility Disclosure - Adeline Kurniawan; Irwanto Handojo (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to examine the effect of board size, independent commissioner, commissioner’s age, and commissioner’s gender on corporate social responsibility disclosure.The sample used in this study is 213 data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) consistently from 2018 to 2020. The sampling method used is the purposive sampling method. Data analysis was carried out with the help of SPSS version 25 program.The results shows that board size has an influence on corporate social responsibility disclosure. Meanwhile, independent commissioner, commissioner’s age, and commissioner’s gender have no influence on corporate social responsibility disclosure.